Anisotropic Magnetoresistance of an Epitaxial Fe Stripe Grown on MgO/GaAs - Shim, Seong Hoon; Kim, Kyung-Ho; Kim, Hyung-Jun; Lee, Yun-Hi; Chang, Joonyeon (AMER SCIENTIFIC PUBLISHERS, 2013)
The anisotropic magnetoresistance of a [100] oriented Fe stripe grown on MgO/GaAs was investigated in order to elucidate the magnetization switching of patterned Fe. A 15 nm thick Fe film was epitaxially grown on MgO/GaAs layers using molecular beam epitaxy and a 50 mu m x 4 mu M shaped Fe stripe was patterned along its magnetic easy axis of [100]. Negative (positive) resistance peaks appear at room (low) temperature in magnetoresistance measurement. A reversal in sign of the peak was evidently observed with decreasing temperature. Such a reversal of resistance peak is caused by the competition between Lorentz force (ordinary) and spin-orbit (extraordinary) dominated scattering processes in a magnetic domain, which is significantly affected by temperature.
Keywords: MAGNETIZATION; IRON